'What is considered good for everyone may not be good for children with Special Educational Needs and Disabilities': teacher's perspectives on inclusion in England. Issue 6 (18th August 2021) - Williams-Brown, Zeta; Hodkinson, Alan
ABSTRACT: This paper reflects on the findings of two studies one completed in 2010 and another in 2019, which employed Q-methodology and post Q-sort semi-structured interviews to an investigation of teachers', in the West Midlands, perspectives of the inclusion agenda. The findings of the 2019 study, demonstrate commonality of findings with that carried out in 2010. The findings reveal that teachers in both studies employed integration and inclusion interchangeably in their attempts to define and operationalise inclusive education. Second, the findings of both studies demonstrate that teachers support inclusion at a theoretical level but in practice find it a difficult concept to operationalise. The 2019 study, though, denotes that a significant barrier to inclusion is whether children with Special Educational Needs and Disabilities (SEND) should or should not be included in SATs. The article details and reflects on the findings of both studies and concludes that the continuous use of SATs needs to be reconceptualise especially in how they enable the inclusion of all children.